PRODUKSI CAKALANG DI WILAYAH PENGELOLAAN PERIKANAN 713 - Putri, Rini Sahni (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2021)
The vast Indonesian sea holds a lot of marine fishery potential that can be utilized by the Indonesian people. In the sea there is the potential for marine resources in the form of fisheries. The Indonesian sea has a large number of sustainable potential, namely 6.4 million tons per year. Skipjack tuna is one of the main targets in fishing activities. One of the Cakalang producing areas in Indonesia is the Fishery Management Area (WPP) 713. WPP-713 is a potential water area in Eastern Indonesia. This study aims to provide a basic overview of Skipjack fishery production in Indonesia and WPP-713. The results of this study indicate that the production value and price of Skipjack tuna in Indonesia has increased from 2005 – 2015. In 2015, the Cakalang price reached IDR 18,164 and a production value of ± IDR 7.54 trillion. Meanwhile, in WPP-713 the average catch production of skipjack tuna shows an increase of 11.4%.